Shariah audit compliance and corporate social responsibility in Malaysia: Islamic banking / Nurul Hamiza Zakaria - Zakaria, Nurul Hamiza (2012)
Islamic banks have offered various services and products to fulfill their social obligations and ethical role as Islamic institutions. Islamic banks are consistently complied with the Shariah Law. Besides that, they are also encouraged to offer Corporate Social Responsibility and Corporate Governance information. The information that is related to the compliance of the Shariah Law needs to be disclosed in their annual report. Besides that, they also need to appoint Shariah auditor (internal auditor and external auditor) to make sure that they comply with Shariah compliance and Corporate Social Responsibility as it already required by Bursa Malaysia. The aim of this study is to identify the level of items disclosed by Islamic bank that related to the Shariah compliance and Corporate Social Responsibility in the annual report. Besides that, the independent variables which are roles of Shariah auditor and their readiness to perform Shariah audit will be measured by analysing the result from the questionnaires that have been emailed and posted to Shariah auditor. There were 120 sets of questionnaire been posted and feedbacks received from 36 of Shariah auditor. The results provide preliminary findings on the disclosures of these three matters pertaining to corporate image improvement and discharging their responsibility as Islamic entity.